2-hour 75 gm OGTT for screening and Rescreening at 32-34 weeks for diagnosing gestational diabetes-evaluation of maternal and neonatal outcomes - Swain, Sujata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational diabetes mellitus, most of which progress to type-2 diabetes mellitus is increasing worldwide. Identification of gestational diabetes and control of glucose can reduce such complications and improve maternal and neonatal health. Methods: A hospital based cross sectional study was conducted to find out maternal and fetal outcome of gestational diabetes from January 2014 to September 2015. Data were collected from 500 antenatal women screened out of which 25 had gestational diabetes and 35 women had intermediate hypergylcaemia attending Sriram Chandra Medical College and Hospital Cuttack for delivery. Results: In our study out of 500 patients, 25 mothers were diagnosed as GDM; its prevalence is 5% in our hospital. In GDM group 10 patients out of 25 had history of risk factors, which constitutes 40 % of the patients. The age group at risk of getting gestational diabetes in this study was between 20-35 years in 98.5%of cases. All the mothers with gestational diabetes were of low parity. In this study, nearly 56% of mothers with gestational diabetes had a body mass index of greater than 25. Significant numbers of cases were detected by rescreening at 32 to 36 weeks who are screen negative during the initial screening procedure (i.e. 10% in GDM group). Caesarean section rate was more in GDM group, mostly due to obstructed labour, fetal distress, hypertension, big baby. Complications like trauma to the baby, congenital anomaly, still birth of the baby were infrequent in this study. Conclusions: Pregnancy thought to be the most vulnerable stage of women's life and protecting her health along with her fetus during this period yields a positive impact on the health of future generation. Particular attention should be given during antenatal period to initiate screening programme and treatment protocol for gestational diabetic mothers.